Una década de estudios de desarrollo en clave iberoamericana - Begoña Gutiérrez-Nieto; José María Larrú-Ramos; Chaime Marcuello-Servós (Revista Iberoamericana de Estudios de Desarrollo)
The Iberoamerican Journal of Development Studies celebrates ten years. It is time to recognize who supports it, the characteristics that have led it to advance in Development research, in addition to achieving international recognition; and to give thanks to so many people who have supported it and to those who today contribute their great value as a team.